Meteorological Influences on PM2.5 and PM10 Concentrations during Haze Periods in West Sumatra: A Case Study from May to July 2025 - Aditya Prapanca; Muhammad Ansori Hasibuan (Universitas Negeri Semarang, 2026)
Forest and land fires during May–July 2025 in West Sumatra triggered haze events that significantly degraded air quality through increased concentrations of PM2.5 and PM10. This study aims to characterize the temporal variability of PM2.5 and PM10 and to assess the influence of meteorological parameters on particulate matter dynamics during the haze period. The results show a significant increase in PM2.5 and PM10 concentrations during the fire period, with fine particles dominating, as indicated by PM2.5/PM10 ratios exceeding 0.6. PM2.5 and PM10 exhibit a very strong positive correlation, suggesting common emission sources. Although most meteorological parameters display weak correlations with particulate concentrations, multivariate regression reveals that relative humidity and wind speed—particularly in the upper atmospheric layer—significantly influence PM variability. These findings indicate that meteorological conditions act as modulators of particulate concentrations, while forest fire emissions remain the primary driver of elevated PM levels during haze episodes.